Electrospun short fibers: a new platform for cancer nanomedicine applications - Yifan Huang; Mengsi Zhan; Mingwu Shen; Lili Zhang; Xiangyang Shi (Exploration of Drug Science)
With the continuous development of nanomaterials, nanofibers prepared by electrospinning have gradually occupied people’s vision because of their unique advantages, such as crisscross network and extracellular matrix-mimicking structure, high drug loading efficiency, and sustained release kinetics. Traditionally, electrospun fibers are mainly used as filter materials, wound dressings, and tissue engineering scaffolds, while their wide applications are limited to cancer nanomedicine applications due to their dense network structure. In recent years, two-dimensional fiber membranes have been transformed into short fibers that can be reconstructed to form fibrous rings or microspheres for cancer theranostics. Herein, this paper provides an overview of the recent advances in the design of electrospun short fibers that retain the advantages of nanofibers with good dispersibility for different nanomedicine applications, including cancer cell capture, cancer treatments, and cancer theranostics. The rational preparation of electrospun short fibers that are available to boost the development of nanomedicine is also discussed.